LÍMITES LEGALES Y JURISPRUDENCIALES DE ACCESO A LA PENSIÓN GRACIA DE LOS DOCENTES NACIONALES (2016)
Raises on the panorama the pension of grace created in his moment by the Law 114 of 1913 in favour of official primary educators that were fulfilling with a minimum of twenty (20) years service and fifty (50) of age, and that for mandate of this law was compatible with the ordinary pension of retirement of departmental character.By later laws this presentation was extended to the employees and teachers of normal and inspectors of instruction (Law 116 of 1928), and also it was allowed complete the years of service in establishments of secondary education (Law 37 of 1993)By effect of these laws the above-mentioned pension was extended to educators of the national order, in spite of which, in the more recent years interpretive problems were generated on having doubted on if it turns out feasible that the teachers lately above-mentioned were receiving the pension grace in addition to the ordinary pension of national character to which they have right. In his moment, this problem solved with the approval of the Law 91 of 1989, which stopped to except the right of the educators linked before December 31, 1980. Nevertheless, with posteriority, has been supported the incompatibility of these two pensions, interpretation that came to be prevalente in the subsequent years.